Functional Performance of Modified Porous Asphalt Mixtures with Gilsonite Additive - Tetra Oktaviani; Dina Tri Septiningtiyas; Wirdatun Nafiah Putri (Jurnal Inotera, 2024)
Porous asphalt is an asphalt mixture with more voids than other asphalt mixtures of a surface layer of a typical flexible pavement structure. Porous asphalt mixtures have several advantages, namely the voids contained in the porous asphalt mixture function to help drain water vertically and horizontally, providing greater skid resistance. In addition to these advantages, the disadvantage of porous asphalt mixtures is the low stability value caused by the large number of voids in the porous asphalt mixture. Because porous asphalt mixtures have many advantages, to increase the stability value of porous asphalt mixtures, one of the methods used is by adding gilsonite. The method used in this research is an experimental method with a labortorium scale. The tests carried out in this study were in the form of skid resistance tests. The porous asphalt mixture in this study used 2 gradations, namely Japanese and Australian gradations.The test specimens used in this mixture are mixtures with optimum asphalt content and 0% gilsonite content. While the modified porous asphalt pavement is a mixture of gilsonite and pen 60/70 asphalt with gilsonite content and optimum asphalt content of 5.5% each. The results showed that the functional performance improvement of the modified asphalt pavement for Japanese and Australian gradations was 14.5% and 2.7%, respectively. Thus, there is an increase in the magnitude of skid resistance values from 55 BPN to 63 BPN and from 75 BPN to 77 BPN or by 8.0 BPN and 2.0 BPN for Japanese and Australian gradations, respectively. This increase in skid resistance value will provide a better level of safety for vehicle users.